2005
DOI: 10.1103/physrevlett.95.196102
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and Phosphorescence from IndividualC60Molecules Excited by Local Electron Tunneling

Abstract: Using the highly localized current of electrons tunneling through a double barrier Scanning Tunneling Microscope (STM) junction, we excite luminescence from a selected C60 molecule in the surface layer of fullerene nanocrystals grown on an ultrathin NaCl film on Au(111). In the observed luminescence fluorescence and phosphorescence spectra, pure electronic as well as vibronically induced transitions of an individual C60 molecule are identified, leading to unambiguous chemical recognition on the single-molecula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(136 citation statements)
references
References 29 publications
7
128
1
Order By: Relevance
“…23,55 Photon emission spectroscopy with the STM, where local optical modes are excited by electron/hole injection from the tip, offers the required spatial resolution. The potential of this technique has already been demonstrated with experiments performed on single molecules, 124,125 metal particles 119,134 and quantum dots, 121 while comparable studies on the oxide materials are still scarce. 51,82,119 Photon emission spectroscopy with the STM will however develop into a versatile tool to explore the local optical properties and their interrelation with the photo-catalytic performance of oxide materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,55 Photon emission spectroscopy with the STM, where local optical modes are excited by electron/hole injection from the tip, offers the required spatial resolution. The potential of this technique has already been demonstrated with experiments performed on single molecules, 124,125 metal particles 119,134 and quantum dots, 121 while comparable studies on the oxide materials are still scarce. 51,82,119 Photon emission spectroscopy with the STM will however develop into a versatile tool to explore the local optical properties and their interrelation with the photo-catalytic performance of oxide materials.…”
Section: Discussionmentioning
confidence: 99%
“…in semiconductors, 120,121,122 oxides, 51 quantum wells 123 and single molecules. 124,125 Common to both scenarios is the crucial role of the electromagnetic near-field in the tip-sample cavity, which amplifies the emission cross-section. 126,127 Thanks to this field enhancement, light emission from an STM junction becomes an observable effect, in spite of the extremely local character of the measurement (~nm 2 ), the small electron flux from the tip (~nA) and the finite number of optical modes involved.…”
Section: Photon Emission Spectroscopy With the Stmmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth and characterization of two-dimensional ordered supramolecular structures on ultrathin NaCl films has only been achieved in very few studies [11][12][13], which is due to experimental difficulties related to the low molecular adsorption energy on such insulating layers. All three mentioned studies were performed on NaCl islands having similar morphological characteristics as the ones observed here on Au(1 1 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that, upon adsorption of molecules on ultrathin NaCl films on metal surfaces, inherent electronic and optical properties of individual molecules can be studied [8][9][10]. However, to our knowledge, there are only three published STM studies on the growth of two-dimensional molecular islands on insulating NaCl layers, two of them on metal-containing porphyrine molecules [11,12], and the third one on C 60 molecules [13]. The small number of investigations about adsorbates on NaCl layers is at least partly due to weak molecule-substrate interactions, which make the stabilization and STM imaging of such systems a challenging task.…”
Section: Introductionmentioning
confidence: 95%